2021
DOI: 10.1590/1516-3180.2020.0346.r1.18112020
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the efficacy of Tai Chi for treating rheumatoid arthritis: an overview of systematic reviews

Abstract: BACKGROUND: Rheumatoid arthritis (RA) is a chronic disease with higher prevalence among women aged between 30 and 50 years and general prevalence of 1% worldwide. Interventions promoting improvement of quality of life for individuals with RA are required. Tai Chi appears to be a low-cost alternative, with studies showing positive results from this technique. However, regarding aspects of RA such as pain and sensitivity, studies remain inconclusive. OBJECTIVES: To compare the effectiveness of the Tai Chi method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Due to the large number of SRs, most of which were screened using a partially blinded process to help reduce the risk of selective reporting bias, it is possible that some populations and outcomes were also missed. However, we are con dent that we have reported the important outcomes also highlighted in other SRs of SRs [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Strengths and Limitations Of This Overviewmentioning
confidence: 89%
See 2 more Smart Citations
“…Due to the large number of SRs, most of which were screened using a partially blinded process to help reduce the risk of selective reporting bias, it is possible that some populations and outcomes were also missed. However, we are con dent that we have reported the important outcomes also highlighted in other SRs of SRs [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Strengths and Limitations Of This Overviewmentioning
confidence: 89%
“…Given the large number of SRs of Tai Chi, SRs of SRs (henceforth referred to as overviews) are increasingly being conducted [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Some have evaluated multiple interventions for a single condition [18][19][20][21][22][23][24][25][26], whilst others have focused only on Tai Chi interventions for either a single condition [7][8][9][10][11][12] or multiple conditions [13][14][15][16][17]. Limitations of the overviews evaluating only Tai Chi interventions [7][8][9][10][11][12][13][14][15]...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study by Imoto et al [321] concluded that tai chi could be a low-cost alternative to other treatments of RA. Their study consisted of a review of three other studies.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Over the past 30 years, a multitude articles have reported the potential benefits of tai chi for health in different populations (1). Numerous meta-analyses and systematic reviews have been performed to explore the efficacy of tai chi practices on falls prevention (4)(5)(6), cardiorespiratory fitness (CRF) (7,8), chronic musculoskeletal pain (9,10), rheumatoid arthritis (11,12), psychological well-being (13,14), and cognitive function (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%